The Implementation of Life Saving Facilities at RSUD Surabaya East Java Province in 2023 - Nurmayanti, Demes; Nadziroh, Umi; Kriswandana, Ferry; Setiawan, Setiawan (Jurnal Teknokes, 2023)
The implementation of life-saving facilities is crucial to be considered in a hospital in order to minimize adverse events during emergency conditions. This study aims to describe the implementation of life-saving facilities at RSUD Suraabaya, East Java Province. The research utilizes a descriptive method with data collection through observation and measurement. The research subject is located at RSUD Surabaya, East Java Province, with the K3RS organization as the respondent. The variables examined include the identification of potential fire hazards and life-saving facilities such as emergency stairs, emergency doors, emergency lights, exit routes, exit signs, and assembly points. Data analysis is conducted descriptively. The research findings indicate that the identification of potential fire hazards in both the New and Old Buildings under normal conditions is in accordance with the applicable Standard Operating Procedures (SOP). Emergency stairs and emergency doors fall under the category of being sufficient, emergency lights fall under the category of being insufficient, while the exit routes, exit signs, and assembly points fall under the category of being good. Overall, theassessment of life-saving facilities falls under the category of being sufficient. Therefore, it is recommended that RSUD Surabaya, East Java Province, conducts monitoring regarding the compliance with SOP, carries out improvements, and procures life-saving facilities that do not meet the requirements. In future research, improvements need to be made by adding other variables. This is necessary in order to correct deficiencies in this research.